Zielgerichtete Erstdiagnostik bei Typ-1-Diabetes - Kalscheuer, Hannes; Lehnert, Hendrik (DMW - Deutsche Medizinische Wochenschrift, 2017)
The incidence of type 1 and type 2 diabetes mellitus has been increasing simultaneously. Formerly, these two patients’ populations could be differentiated easily, but now, due to the overlapping of both groups, specified diagnostics are necessary. In order to substantiate a suspicion on diabetes, quantifying venous plasma glucose is the gold standard in diagnostics. As a precaution, determination of the HbA1c and OGTT is recommended. It is not necessary to determinate antibodies in every new case of diabetes. In patients with a vague constellation of clinical picture diagnosis can be ensured by findings of uric ketones, BGA, IA-2- and GAD-antibodies and optionally C-peptide. Often T1DM is associated with PGAS. Therefore, once manifestation of diabetes is detected, screening autoimmune disorders is recommended directly and regularly every two years.
Keywords: Typ-1-Diabetes; Erstmanifestation; Differenzialdiagnose; Diagnostik; Autoimmunität